RANCANG BANGUN SISTEM INFORMASI KONSULTASI AKADEMIK MAHASISWA JURUSAN BERBASIS WEB PADA STMIK PRASTIKOM - Sutrisno Sutrisno; Rohmawati Ningsih (UNIVERSITAS RAHARJA, 2018)
The world of education in college is expected to be a world of human development for civilization. Students are equipped with knowledge of education based on the needs of the era. In line with the needs of students, not infrequently there are students who have difficulty in completing certain courses. Difficulties that vary from the beginning of the semester to the final semester, the difficulty in terms of learning activities on campus or even association in the campus environment. To be able to answer these questions required an application that can bridge the needs of students with faculty majors. This web design also aims to provide solutions to student problems and build student motivation in completing their education on time. With the academic consultation web is expected to make lecturer services to be maximal, students are motivated to complete the lecture and reduce the failure rate of students in completing the lecture. Data collection method used in this journal is qualitative method, that is by doing observation, interview, and literature study. With the web majors are expected to be a means of closeness between lecturers and students in relation to teaching and learning proximity between students in the same department although different levels.